Cross-Sectional Analysis of Alcohol Intake and Serum Antibodies to Oral Microorganisms. (April 2017) - Merchant, A.T.; Park, Y.M.; Dodhia, S.; Shrestha, D.; Choi, Y.H.; Pitiphat, W.
The objective of this study was to evaluate the relation between alcohol intake and groups of periodontal antibody titers among individuals with normal glucose tolerance (NGT), prediabetes and diabetes. This was a cross-sectional analysis of the National Health and Nutrition Examination Survey III (NHANES III) 1988–1994 data, among individuals 40 y and older with information on alcohol intake and serum immunoglobulin G (IgG) antibody data against 19 oral microorganisms. Participants were excluded if they did not have teeth, reported that they were taking insulin, or having gestational diabetes. The sample size for this analysis was 3, 219. Periodontal antibodies were grouped into four clusters using cluster analysis: Orange-Red, Red-Green, Yellow- Orange, and Orange-Blue. Cluster scores were computed for each individual by summing z-scores of standardized log-transformed IgG titers of antibodies against periodontal microorganisms making up each respective cluster. Each cluster score was modeled as an outcome. Alcohol consumption was assessed in g/day using self-reported number of days of drinking in the past 12 mo and the average number of drinks consumed per day on days when they drank. Overall, alcohol intake was positively associated with periodontal antibodies of the Orange-Red cluster (P. melaninogenica, P. intermedia, P. nigrescens, and P. gingivalis), and inversely associated with the Yellow-Orange cluster (S. intermedius, S. oralis, S. mutans, F. nucleatum, P. micra, C. ochracea) after multivariable adjustment. The association between alcohol intake and the Orange-Red cluster was strongest among individuals with diabetes; this relation was seen among individuals with and without periodontal damage. The Orange-Red cluster was positively associated with periodontal damage among individuals with diabetes. Alcohol intake was not associated with any antibody cluster among individuals with NGT or prediabetes. The effect of alcohol intake on periodontal disease may be greater among individuals with diabetes but this finding needs to be confirmed in prospective studies. Knowledge Transfer Statement: The results of this study can be used by clinicians when treating patients with periodontal disease and diabetes.